Free convection analysis for a nanofluid in a wavy porous domain subject to shape of nanoparticle and internal heat generation - Fereidooni, Jalil (International journal of modern physics. B, Condensed matter physics, statistical physics, applied physics, 2024)
Natural convection takes up the attention of researchers due to its expansive industrial and engineering utilizations i.e., heat exchangers and electronic cooling. In this work, free convection of Cu-H2O nanoliquid flow and heat transfer (HT) in porous circular wavy domain under the internal heat generation has been perused by finite element method (FEM). The shape factor of nanomaterials is also considered. The influences of active factors like Rayleigh number Ra, nanofluid concentration, wavy wall’s contraction ratio A, number of undulations D, and shape factor of nanomaterials m are explored on flow and HT specifications. Moreover, the correlations for average Nusselt number Nuave have been attained with regard to impressive parameters of current study. Findings show that Nuave soars with soaring nanofluid concentration and nanoparticles’ shape factor. Further, the outcomes characterize that Nuave may lessen up to 15.11% and 9.95% by detracting A from 0.1 to 0.3 and by mounting D from 4 to 12, respectively.